1986
DOI: 10.1111/j.1151-2916.1986.tb04839.x
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium Segregation and YAG Precipitation at Surfaces of Yttrium‐ Doped α‐A12O3

Abstract: presented in Figs. 3(B) and (C), indicate that the phase in bright contrast in Fig. 3(A) contains both yttrium. and aluminum while the phase in dark contrast in Fig. 3(A) is rich in aluminum but devoid of yttrium.The work of Loudjani et al., ' un ublished work of McCune and Donlon, and the YZ03-A1203 phase diagram3 all suggest that the phase in bright contrast is Y3AI5Ol2. Apparently the solubility of yttrium in N203 is extremely low and the dopant was rejected to the melt during crystal growth until the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…The underlying atomic scale mechanisms are, however, still speculated upon, the following literature review showing possible explanations for this so‐called Y effect. It is well known that Y strongly segregates to α‐alumina surfaces and that its solubility in the bulk is very limited (∼10 atomic ppm) 3,4 . Imaging‐SIMS confirmed Y dopants in α‐alumina ceramics to be located mainly at grain boundaries and free surfaces in pores 5 .…”
Section: Introductionmentioning
confidence: 89%
“…The underlying atomic scale mechanisms are, however, still speculated upon, the following literature review showing possible explanations for this so‐called Y effect. It is well known that Y strongly segregates to α‐alumina surfaces and that its solubility in the bulk is very limited (∼10 atomic ppm) 3,4 . Imaging‐SIMS confirmed Y dopants in α‐alumina ceramics to be located mainly at grain boundaries and free surfaces in pores 5 .…”
Section: Introductionmentioning
confidence: 89%
“…First, Cawley and Halloran (49) demonstrated recently, using yttrium-doped sapphire from the same lot employed by EI-Aiat and Kroger (48), that the solubility of yttrium in these A1203 single crystals is lower than that of other impurities. (50) also demonstrated that the solubility of yttrium in A1203 is extremely low. Measurements by McCune et at.…”
Section: February 1988mentioning
confidence: 94%
“…Due to its limited solubility in alumina crystal lattice ($ 10 at ppm) yttrium segregates to alumina/alumina interfaces [32,33]. Large yttria cations segregated at the interfaces block the motion of Al 3 þ and O 2À ions along grain boundaries, which results in reduced grain-boundary diffusivity and decreased densification rate [34].…”
Section: Introductionmentioning
confidence: 99%